Endogenous Retrovirus-Derived Long Noncoding RNA Enhances Innate Immune Responses via Derepressing RELA Expression - Bin Zhou; Fei Qi; Fangyi Wu; Hongbo Nie; Yifan Song; Lu Shao; Jingxuan Han; Zhen Wu; Hexige Saiyin; Gang Wei; Penghua Wang; Ting Ni; et al. (mBio, 2019)
ABSTRACT Endogenous retroviruses (ERVs) are transposable elements that cause host genome instability and usually play deleterious roles in disease such as tumorigenesis. Recent advances also suggest that this “enemy within” may encode a viral mimic to induce antiviral immune responses through viral sensors. Here, through whole-genome transcriptome analysis with RNA sequencing (RNA-Seq), we discovered that a full-length ERV-derived long noncoding RNA (lncRNA), designated lnc-EPAV (ERV-derived lncRNA positively regulates antiviral responses), was a positive regulator of NF-κB signaling. lnc-EPAV expression was rapidly upregulated by viral RNA mimics or RNA viruses to facilitate the expression of RELA, an NF-κB subunit that plays a crucial role in antiviral responses. Transcriptome analysis of lnc-EPAV-silenced macrophages showed that lnc-EPAV was critical for RELA target gene expression and innate immune responses. Consistently, lnc-EPAV-deficient mice exhibited reduced expression of type I interferons (IFNs) and, consequently, increased viral loads and mortality following lethal RNA virus infection. Mechanistically, lnc-EPAV promoted expression of RELA by competitively binding to and displacing SFPQ, a transcriptional repressor of Rela. Altogether, our work demonstrates an alternative mechanism by which ERVs regulate antiviral immune responses. IMPORTANCE Endogenous retroviruses are transposable genetic elements comprising 8% to 10% of the human and mouse genomes. Although most ERVs have been inactivated due to deleterious mutations, some are still transcribed. However, the biological functions of transcribed ERVs are largely unknown. Here, we identified a full-length ERV-derived lncRNA, designated lnc-EPAV, as a positive regulator of host innate immune responses. We found that silencing lnc-EPAV impaired virus-induced cytokine production, resulting in increased viral replication in cells. The lnc-EPAV-deficient mice exhibited enhanced susceptibility to viral challenge. We also found that lnc-EPAV regulated expression of RELA, an NF-κB subunit that plays a critical role in antiviral responses. ERV-derived lncRNA coordinated with a transcription repressor, SFPQ, to control Rela transcription. Our report provides new insights into the previously unrecognized immune gene regulatory mechanism of ERV-derived lncRNAs.